2014
DOI: 10.1089/aid.2013.0074
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Transmitted HIV Drug Resistance in Antiretroviral-Naive Pregnant Women in North Central Nigeria

Abstract: The World Health Organization (WHO) recommends periodic surveillance of transmitted drug resistance (TDR) in communities in which antiretroviral therapy (ART) has been scaled-up for greater than 3 years. We conducted a survey of TDR mutations among newly detected HIV-infected antiretroviral (ARV)-naive pregnant women. From May 2010 to March 2012, 38 ARV-naive pregnant women were recruited in three hospitals in Jos, Plateau state, north central Nigeria. Eligible subjects were recruited using a modified version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
6
13
0
Order By: Relevance
“…This analysis may represent one of the largest HIV genotypic analyses at the population level across Nigeria. These are in agreement with other HIV-1 subtype studies in this region [610, 2830]. …”
Section: Discussionsupporting
confidence: 93%
“…This analysis may represent one of the largest HIV genotypic analyses at the population level across Nigeria. These are in agreement with other HIV-1 subtype studies in this region [610, 2830]. …”
Section: Discussionsupporting
confidence: 93%
“…This rate is in agreement with the rates reported in Jos, in the Plateau State, 40 and the North Central region of Nigeria. In the protease region, one sample displayed the K43T mutation, which was associated with a decreased virological response to tipranavir boosted with ritonavir (TPV/r) in the RESIST trials.…”
Section: Discussionsupporting
confidence: 92%
“…16,18,34,3840 In a study published in 2000, subtype A was predominant (about 70%) in the southwest-Lagos state and subtype G was predominant in the northwest-Kano state (about 58%), while both subtypes A (49%) and G (47%) were observed to be equally distributed in the northeast (Maiduguri). 18 In 2006, a study in Oyo state (southeast) showed the predominance of CRF02-AG (57%), subtype G (26%), and CRF06-cpx (11%), 16 and similar results with 39–45% for CRF02-AG and 38% for subtype G were reported in 2009 41 and 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of occurrence (10.7%) of major PI resistance mutations, M46L and V82L, obtained in this study is somewhat lower than the 39.1% recorded in a similar study conducted by Odaibo et al [17] on pattern of HIV-1 drug resistance among adults on ART in Nigeria. However, some other studies conducted in different parts of the country on both drug naïve and experienced patients reported no major PI resistance mutations [18,19]. Acquisition of PI resistance is known to be cumulative in nature requiring sequential accumulation of mutations in the setting of on-going exposure to non-suppressive PI-based ART [27,28]), therefore the appreciable level of IAS PR mutation detected among the patients in our study is a serious cause for concern as it places them at increased risk of accumulating additional PI resistance mutations.…”
Section: Discussionmentioning
confidence: 92%
“…There is however comparatively little available data from less developed countries where non-B subtypes predominate. In Nigeria where the epidemic is largely driven by non-B subtypes, reports on HIV drug resistance and polymorphisms [12][13][14][15][16][17][18][19][20][21] have primarily focused on resistance to non-nucleoside reverse transcriptase inhibitors (NNRTIs) and nucleoside reverse transcriptase inhibitors (NRTIs) while resistance to Protease inhibitors (PI) remain understudied. Since the commencement of ART program in Nigeria in 2001, government has collaborated with some donor agencies such as Global Fund to Fight AIDS, Tuberculosis, and Malaria and US President's Emergency Plan for AIDS Relief (PEPFAR) to scale up its ART clinics.…”
Section: Introductionmentioning
confidence: 99%